MEASURING SYSTEMS BASED ON TWO-WAVELENGTH SEMICONDUCTOR LASERS AND CONCEPT OF «A PRIORI INFORMATION ELIMINATION» - V. L. Kozlov; M. M. Kygeiko (Приборы и методы измерений)
Construction principles of highly effective measuring systems based on two-wavelength semiconductor lasers and the concept «a priori information elimination» are presented. These systems provide advantages before similar one-wavelength laser measuring instruments.